THE WAY TOWARDS OPEN INNOVATION: AIRBUS MULTI-FUNCTIONAL TEAMS - Allal-Chérif, Oihab (European Scientific Journal, ESJ, 2015)
In times of crisis, innovation is a key to differentiation and thus to the survival of businesses. However, actions taken by managers to stimulate creativity are essentially within the framework of a conventional closed innovation made only internally. Yet, open innovation is a much more efficient and economical way to develop new products, new materials, new technologies and new methods. It requires that partner organizations operate in an open network in which they can work together, each bringing their expertise and talents. This is usually the purchasing function, transverse and connected to the business environment, which can best orchestrate this open innovation by selecting the best suppliers to work with them within new models of integration more or less advanced. The case study of the company Airbus, developed during a participant observation of one year, will define the role of the procurement function in this open innovation approach and the benefits, hazards and limits of this strategy. Examples of the design of the A380 and of the Technocampus EMCÂ² environment illustrate the integrated supplier relationship management method combined with open innovation.